STABLE-CARBON ISOTOPE COMPOSITION OF POACEAE POLLEN: AN ASSESSMENT FOR RECONSTRUCTING C3 AND C4 GRASS ABUNDANCE - Nelson D.M.; Hu F.Sh.; Michener R.H. (My University, 2006)
Plants using the C3 and C4 photosynthetic pathways differ in carbon-isotope composition, and this difference offers a means to estimate the relative abundance of these two functional groups in the palaeorecord. We report here results of a study aiming to evaluate pollen ?13C(?13Cp) of Poaceae (the grass family) as a proxy indicator for palaeoecological studies. On average ?13Cp differs by ? 13- between modern C3 (-22.6 to - 26.8) and C4 (-9.2 to -17.7) grass species. ?13Cp is 1.2-3.7 more negative for modern grass pollen treated with the same protocol as for fossil samples than for untreated modern samples. ?13Cp ranges from -20.1 to -25.4 for grass pollen in the middle-Holocene sediments from West Olaf Lake, located near the modern tallgrass prairie forest ecotone in western Minnesota. We applied a two end-member mixing model to estimate fluctuations in C3 and C4 grass abundance around this lake. Both C3 and C4 grasses expanded relative to Ambrosia and Artemisia with the decline of aridity from 8000 to 4000 BP. C3 grasses were generally more abundant than C4 grasses throughout the middle Holocene, suggesting the presence of mixed-grass prairie around West Olaf Lake. The grass ?13Cp-based estimates of C4 plant abundance were lower than charcoal ?13C-based estimates, probably reflecting different source areas of pollen and charcoal. Grass ?13Cp also revealed greater submillennial-scale variability in C3 and C4 abundance than charcoal ?13C. These results suggest that grass ?13Cp can provide palaeoenvironmental information not available from other proxy indicators.
Keywords: STABLE-CARBON ISOTOPE; δ13C; POACEAE; C3 AND C4 GRASSES; PRAIRIE; PALAEOECOLOGY; POLLEN; PALYNOLOGY; MODERN ANALOGUE; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен